Dose-Dependent Acute Circulatory Fates Elicited by Cadmium Are Mediated by Differential Engagements of Cardiovascular Regulatory Mechanisms in Brain - Chen, Shu-Mi; Phuagkhaopong, Suttinee; Fang, Chi; Wu, Jacqueline C. C.; Huang, Ya-Hui; Vivithanaporn, Pornpun; Lin, Hsun-Hsun; Tsai, Ching-Yi (Frontiers in Physiology, 2019)
Whereas cadmium is a toxicant that has been shown to cause cardiovascular toxicity and mortality in mammals, few mechanistic studies address its acute circulatory actions. The present study assessed the hypothesis that cadmium effects dose-dependent acute circulatory fates via differential participation of the cardiovascular regulatory mechanisms in brain. In Sprague-Dawley rats maintained under propofol anesthesia, cadmium acetate (8 mg/kg, iv) induced significantly high mortality rate within 10 min, concomitant with progressive decline towards zero level of mean arterial pressure (MAP), heart rate (HR), baroreflex-mediated sympathetic vasomotor tone, and carotid blood flow. There were concurrent tissue anoxia, cessation of microvascular perfusion, reduction of mitochondrial membrane potential and ATP production, and necrotic cell death in the rostral ventrolateral medulla (RVLM), the brain stem site that maintains blood pressure and sympathetic vasomotor tone. On the other hand, a lower-dose of cadmium (4 mg/kg, iv) resulted in only a transient decrease in MAP that was mirrored by an increase in carotid blood flow and baroreflex-mediated sympathetic vasomotor tone, minor changes in HR, along with transient hypoxia and apoptotic cell death in RVLM. We conclude that cadmium elicits dose-dependent acute cardiovascular effects with differential underlying biochemical and neural mechanisms. At a higher-dose, cadmium induces high mortality by effecting acute cardiovascular collapse via anoxia, diminished tissue perfusion, mitochondrial dysfunction and bioenergetics failure that echo failure of cerebral autoregulation, leading to necrosis and loss of functionality in RVLM. On the other hand, a lower-dose of cadmium elicits low mortality, transient decrease in arterial pressure, and hypoxia and apoptosis in RVLM that reflect sustained cerebral autoregulation.